Measurement of sound level in sports clubs with the approach of maintaining the health of athletes - Ling-Hsiang Chang; Hooman Bahmanpour; Ali Fahiminejad (Anthropogenic Pollution)
The purpose of this study is to measure the sound level in bodybuilding clubs in Mashhad with the approach of maintaining the health of athletes. The metropolis of Mashhad, the capital of Khorasan Razavi province, is located in northeastern Iran. Fifteen bodybuilding clubs were randomly selected by networking method. The sound level in the clubs was measured in level A and as an equivalent level by the portable device and software Decibel X version 2019 and was compared with the sound standard (OSHA-90 dBA). Measurements were made in the morning and evening. The parameters of sound pressure level (SPL), mean sound level (LP) Ìcontinuous sound equivalent level (Leq) and individual daily dose of LAEp, d were calculated. The lowest sound pressure level in the morning was 76.5 decibels and the highest pressure level in the evening was 99.4 decibels. There was a direct relationship between sound pressure level and athletes' time in the club. The average sound level in sports clubs is equal to 87.6 dB and the level is equal to 90.61 and the daily individual dose of LEp, d athlete in the club is equal to 84.58 dB. The permissible duration of exposure to noise for athletes was estimated at 1 hour and 40 minutes. In the gymnasiums of Mashhad, athletes are exposed to high noise pollution and the possibility of physical and mental injuries is high.